Calculation of the systematic vertical drainage under protection of the irrigated lands and built-up territories from the ground waters submergence - Telyma, Sergii V. (ІТГІП, 2018)
The methodic of the solution of the problem of the transient flow in multilayer heterogeneous in cross section aquifer at modeling of the vertical drainage work with different boundary conditions on the contour of the drainage well is proposed. The numerical aspects of the solution of the given problem and the example of solution the methodic task for scheme of the three-layer aquifer at the constant drawdown of the ground and underground waters on the well contour are considered.
Keywords: analytical solution; transient flow; numerical algorithm; vertical drainage; multilayer aquifer; 551.49.001.57; 627.8:532.546.626